KEWENGANGAN PENGADILAN TATA USAHA NEGARA DALAM PENYELESAIAN SENGKETA PEMILIHAN UMUM KEPALA DAERAH - HB, Gusliana; Indra, Mexsasai; ', Grace (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The general elections to choose Regional Head and Regional Head Vice (regional election) directly by the people under the Act (the Act) 32 of 2004 on Regional Government, as amended by Act 12 of 2008 in conjunction with the Government Regulation (PP) No. .6 in 2005, seen as a step forward in the democratic political system in our country, in order to realize the ideals of the Unitary Republic of Indonesia (Indonesian Republic) safe, orderly, fair and prosperous. However, after five years of direct election was held in the Republic (as of the month of June 2005 under the provisions of Article 233 paragraph 1 of Law 32 of 2004), it's almost always tinged with the negative impact of the various violations that gave birth to the dispute and contention, whether conducted by the contestants and supporters as well as those conducted by the organizers (Election Commission) itself.Keywords: Authority –PTUN- Dispute – Regional Election